Sulfur Dioxide Control by Electric Utilities: What Are the Gains from Trade? - Carlson, Curtis; Burtraw, Dallas; Cropper, Maureen; Palmer, Karen L. (Journal of Political Economy, 2000)
Title IV of the 1990 Clean Air Act Amendments (CAAA) established a market for transferable sulfur dioxide (SO2) emission allowances among electric utilities. This market offers firms facing high marginal abatement costs the opportunity to purchase the right to emit SO2 from firms with lower costs, and is expected to yield cost savings compared to a command and control approach to environmental regulation. This paper uses econometrically estimated marginal abatement cost functions for power plants affected by Title IV of the CAAA to evaluate the performance of the SO2 allowance market. Specifically, we investigate whether the much-heralded fall in the cost of abating SO2, compared to original estimates, can be attributed to allowance trading. We demonstrate that, for plants using low-sulfur coal to reduce SO2 emissions, technical changes and the fall in low-sulfur coal prices have lowered marginal abatement cost curves by over 50% since 1985. The flexibility to take advantage of these changes is the main source of cost reductions, rather than trading per se. In the long run, allowance trading may achieve cost savings of 700-800 million per year compared to an "enlightened" command and control program characterized by a uniform emission rate standard. The cost savings would be twice as great if the alternative to trading were forced scrubbing. However, a comparison of potential cost savings in 1995 and 1996 with actual emissions costs suggests that most trading gains were unrealized in the first two years of the program.